Truth, testimony, and self-deception. (1st September 2020) - Zapero, David
Abstract : The essay explores Richard Moran's conception of the self-relation that certain social interactions involve. My focus is on the following question: how much room is there for being deceived about how one presents oneself to others when providing testimony and how does such self-deception – if indeed it exists – relate to other forms of self-deception? Before addressing these two issues (Sections 2 and 3 respectively), I take a detour (Section 1) and inquire into how truth matters for the success of testimony.